INTERVENSI FISIOTERAPI PADA KASUS ASMA BRONKHIAL DENGAN LATIHAN YOGA - Deffani Octa Valentina (2022)
Asthma Bronchiale is one of the many diseases in our society. The disease can attack anyone from the lower classes of society or even upper classes, children or adults, man or woman and it can causes a death to every adults. People who have asthma bronchiale will experience shortness of breath especially when inhaling allergens. Purpose : The purpose of this study is to prove the effectiveness of yoga exercise in reducing suffocation in asthma bronchiale sufferers. Research Methods : This study used a quantitative type of research with descriptive methods. The study was conducted on 1 person clients who have conditions as needed for the research. The results of this study is we obtained a reduction in the degree of suffocation by 2 scales with Borg scale and 1 scale with mmRC scale. The body's oxygen saturation increases and the respiratory rate improves as it gives yoga exercise. Conclution : The conclusion of this study is that the client's condition has not shown a good change in the first 3 days of exercise. However, the next day a considerable development was obtained and the client felt his condition was better when working.